Presentación - Assalone, Eduardo (ARFIL y UNL, 2021)
On the occasion of the two hundred and fiftieth anniversary of the birth of G. W. F. Hegel (1770-1831) and the bicentenary of the publication of the Philosophy of Right, the Hegelian Studies Group (Institute of Philosophy Alejandro Korn, University of Buenos Aires) promotes and elaborates this dossier dedicated to the reconstruction of the history of Argentine Hegelianism. To this end, this dossier contains seven articles exploring key moments in the interpretation and appropriation of Hegelian philosophy in our country, as well as an interview with Prof. Dr. Daniel Brauer, one of the researchers who has devoted important studies to Hegel's thought and has contributed to its reception in Argentina.